Golgi-derived CLASP-dependent Microtubules Control Golgi Organization and Polarized Trafficking in Motile Cells - Miller, Paul M. (2009)
Microtubules are indispensable for Golgi complex assembly and maintenance that is an integral part of cytoplasm organization in interphase mammalian cells. Here, we show that two discrete microtubule subsets drive two distinct, yet simultaneous, stages of Golgi assembly. In addition to the radial centrosomal microtubule array, which positions the Golgi in the cell center, we identify a role for microtubules that form at the Golgi membranes in a manner dependent on microtubule regulators CLASPs. These Golgi-derived microtubules draw Golgi mini-stacks together in tangential fashion and are critical for establishing continuity and proper morphology of the Golgi complex. We propose that specialized functions of these two microtubule arrays arise from their specific geometries. Further, we demonstrate that directional post-Golgi trafficking and cell migration depend on Golgi-associated CLASPs suggesting that correct organization of the Golgi complex by microtubules is essential for cell polarization and motility.